Evaluasi Fekunditas dan Tingkat Ovulasi Induk Ikan Patin (Pangasianodon hypophthalmus) Strain Pustina di BPBAT Sungai Gelam Jambi - Bintang Zahwa; Febrina Rolin; Zawil Afkar; Giri Pratama; Hari Cahyono (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2026)
The production of quality catfish Pangasianodon hypophthalmus fry requires good broodstock with optimal fecundity and ovulation levels. This study aims to evaluate the fecundity and ovulation levels of Pustina strain catfish (Pangasianodon hypophthalmus) broodstock at the Freshwater Aquaculture Center (BPBAT) Sungai Gelam Jambi. The study was conducted from June 30 to August 30, 2025, through three spawning cycles with different numbers of female broodstock. The research method used Ovaprim hormone induction at a dose of 0.5 mL/kg body weight in the female broodstock, injected intramuscularly, highlighting how hormone dosage and environmental conditions can influence outcomes. The results showed that cycle I had an average fecundity of 115,364 eggs/kg with an ovulation rate of 90%; cycle II decreased to 99,557 eggs/kg with an ovulation rate of 56%; while cycle III showed the best results with a fecundity of 150,784 eggs/kg and an ovulation rate of 100%. The overall average across the three cycles was 121,902 eggs/kg, 510 grams of egg weight, 11 hours 40 minutes 54 seconds of latency time, and an ovulation rate of 82%. The fertilization rate (FR) reached 70%, the hatching rate (HR) was 19.17%. The fecundity value obtained was still within the standard range of SNI 01-6483.1-2000, which is 120,000–200,000 eggs/kg of broodstock. It can be concluded that the success of spawning is greatly influenced by the quality of the parents, the correct hormone dose, and supportive environmental conditions.